ANALISIS PENGARUH CAR, NPL, BOPO, LDR, DAN NIM TERHADAP ROA PADA PERUSAHAAN PERBANKAN DI INDONESIA - Anggun Dwi Nurmawati, 08.05.52.0132; Widati, Listyorini Wahyu (Students Journal of Accounting and Banking, 2012)
The study aims to analyze the effect of Capital Adequacy Ratio (CAR), non-performing loans (NPL), Operating Expenses to Operating Income (BOPO) , Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), to the Banking Profitability (ROA). Population in this study is a commercial bank registered in the Bank Indonesia year period 2007-2009. Number of samples were 332 banks registered in the Bank Indonesia. Study sample is taken with certain criteria that companies belonging to banking in general banks in early 2007 to 2009, and the bank has published its financial statements in the year 2007-2009 as well as having a complete variable according to the author of the analysis.The research method used in this study is multiple regression analysis, to test the hypothesis. Before using multiple regression analysis, conducted tests of normality, the assumption of classical test and multiple regression.Based on the results of the feasibility test model using the F test showed that the CAR, NPL, BOPO, LDR, and NIM have a significant effect on ROA in the banking public bank with a significance level of 0.000. Adjusted R Â² value in the regression model obtained for 0.647 bank. This suggests that the major influence of the independent variable is CAR, NPL, BOPO, LDR, and NIM, to the dependent variable (ROA) of 64,7% while the remaining 35,3% influenced by other factors. If the R Â² value closer to 1 the independent variables (CAR, NPLs, BOPO, LDR and NIM) the stronger influence in explaining the bound variable (ROA). While based on the hypothesis test results indicate that the variable CAR, LDR, and NIM significantly positive effect on ROA. NPL negative effect on ROA is not significant. While a significant negative effect BOPOvariables to ROAKey words: CAR, NPL, BOPO, LDR, NIM, ROA